DIFFERENCES IN SPELLING BETWEEN ENGLISH AND FRENCH LEXICAL-SEMANTIC CONNECTION AND DIFFERENTIATION - Safarova Khurshida Salimovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
It is a fact that the most honorable, the greatest, the most immortal scientific and creative works of our people in the world history are actually written in this writing: Spelling is the fate of the nation, the language of historical heritage and the foundation of the future! If we make another mistake, our great ancestors will not forgive us. It is necessary that we spend the life of the society, the nation, and the educational system on tests and not retreat from the original goal.